The interaction of antibiotics with the large ribosomal subunit from Haloarcula marismortui - Moore, Peter (Henry Stewart Talks, 2008)
Introduction to a paradox: how can a universally conserved cellular component be a target for pharmacologically useful antibiotics?, Introduction to ribosome structure, Antibiotic binding sites cluster in the ribosome, The source of the species specificity of antibiotics that interact with the A-site cleft, How macrolides interact with the ribosome, The structural consequences of mutations that make ribosomes resistant to macrolides, The toxicity of macrolides is not well understood, 13-deoxytedanolide, a novel macrolide with novel species specificity that binds to a novel site in the ribosome
Archived at 2021/02/25